The Relationship Between Knowledge, Protein Energy Consumption Levels and KEK Status of Pregnant Women in the Manggis II Community Health Center Area - Ni Putu Ayu Angelita Panely; I Komang Agusjaya Mataram; I Gusti Agung Ari Widarti (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2026)
The objective of this study was to analyze the relationships between nutrition knowledge, levels of energy and protein intake, and the occurrence of Chronic Energy Deficiency (CED) among pregnant women in the catchment area of Puskesmas Manggis II. An observational design with a cross-sectional approach was employed. The study sample consisted of all pregnant women in the area, totaling 37 individuals. Data were collected through interviews, questionnaires, and Upper Arm Circumference (UAC) measurements. Results indicated that the majority of pregnant women were classified as not at risk for CED (86.5%), while 13.5% were at risk for CED (UAC < 23.5 cm). Most sampelts’ nutrition knowledge was categorized as good (89.2%), with the remainder falling into the fair and poor categories (each 5.4%). The majority also demonstrated good energy intake (81.1%), and protein intake was predominantly good (48.6%) or more than adequate (45.9%). Spearman’s correlation analysis revealed a significant positive relationship between nutrition knowledge and energy intake (r = 0.625; p = 0.000), as well as between nutrition knowledge and protein intake (r = 0.468; p = 0.003). Additionally, there were significant positive correlations between energy intake and CED status (r = 0.564; p = 0.000) and between protein intake and CED status (r = 0.480; p = 0.003). These findings underscore that a high level of nutrition knowledge, together with adequate energy and protein intake, plays a crucial role in preventing Chronic Energy Deficiency among pregnant women.